Fire protection engineering for new and existing tunnels delegate information : Friday 6 October 2006. (Thomas Telford, 2006)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held on 6 October 2006.